2022
DOI: 10.3390/biomedicines10010145
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of HP0044 and HP1275 Knockout Mutations on the Structure and Function of Lipopolysaccharide in Helicobacter pylori Strain 26695

Abstract: Helicobacter pylori infection is associated with several gastric diseases, including gastritis, peptic ulcer, gastric adenocarcinoma and mucosa-associated lymphatic tissue (MALT) lymphoma. Due to the prevalence and severeness of H. pylori infection, a thorough understanding of this pathogen is necessary. Lipopolysaccharide, one of the major virulence factors of H. pylori, can exert immunomodulating and immunostimulating functions on the host. In this study, the HP0044 and HP1275 genes were under investigation.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 62 publications
0
7
0
Order By: Relevance
“…Phenotypic characterization of the RS47-2 waaC mutant also confirmed production of a truncated LPS lacking O-antigen, and with changes to the inner core. In addition, alterations to surface hydrophobicity, autoaggregation, and human serum susceptibility in RS47-2 are also congruent with defects in LPS production and loss of O-antigen ( Rowley, 1968 ; Luke et al, 2010b ; Nakao et al, 2012 ; Hu et al, 2021 ; Wang et al, 2021 ; Liu et al, 2022 ). Because disruption to LPS production has also been associated with changes in motility in P. mirabilis ( Gygi et al, 1995 ; McCoy et al, 2001 ; Morgenstein et al, 2010 ), we compared both swimming and swarming motility of RS47-2 to the RS47 WT.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Phenotypic characterization of the RS47-2 waaC mutant also confirmed production of a truncated LPS lacking O-antigen, and with changes to the inner core. In addition, alterations to surface hydrophobicity, autoaggregation, and human serum susceptibility in RS47-2 are also congruent with defects in LPS production and loss of O-antigen ( Rowley, 1968 ; Luke et al, 2010b ; Nakao et al, 2012 ; Hu et al, 2021 ; Wang et al, 2021 ; Liu et al, 2022 ). Because disruption to LPS production has also been associated with changes in motility in P. mirabilis ( Gygi et al, 1995 ; McCoy et al, 2001 ; Morgenstein et al, 2010 ), we compared both swimming and swarming motility of RS47-2 to the RS47 WT.…”
Section: Discussionmentioning
confidence: 81%
“…WaaC has been described as essential for synthesis of the LPS inner core in other species, and its inactivation associated with a truncated LPS lacking O-antigen ( Pearson et al, 2008 ; Wang et al, 2014 ). Loss of O-antigen has also been associated with changes to a range of cell surface associated characteristics relevant to antimicrobial susceptibility and virulence, such as hydrophobicity, autoaggregation, human serum susceptibility, and motility ( Rowley, 1968 ; Gygi et al, 1995 ; McCoy et al, 2001 ; Morgenstein et al, 2010 ; Luke et al, 2010a ; Nakao et al, 2012 ; Hu et al, 2021 ; Wang et al, 2021 ; Liu et al, 2022 ). To confirm the predicted impact of waaC disruption in RS47-2, we compared the LPS structure and associated characteristics of this mutant to the RS47 parental WT.…”
Section: Resultsmentioning
confidence: 99%
“… 13 Similar to our results from a recent study, algC knockout also led to an aberrant core region in H. pylori . 14 However, mutations in LPS synthesis-related genes do not always increase membrane permeability. Our previous study showed that the loss of rfaF encoding lipopolysaccharide heptosyltransferase II, which transfers a second heptose residue into the LPS core, reduced membrane permeability.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the disruption of GDP-fucose synthesis resulted in LPS truncation, thereby increasing the susceptibility of H. pylori to SDS and novobiocin. 14 In this study, we constructed Δ algC and Δ galU mutants of H. pylori and investigated their drug sensitivity, LPS structure, and outer membrane permeability. We found that AlgC and GalU were critical for the intrinsic resistance of H. pylori .…”
Section: Introductionmentioning
confidence: 99%
“…Knockout studies on H. pylori genes HP0044 and HP1275 demonstrated the production of a truncated H. pylori LPS missing fucose residues found in both the trio and Lewis antigen portions of the H. pylori LPS O antigen, resulting in the loss of a significant portion of the H. pylori LPS. This in turn affected the growth of the bacterium, increased its susceptibility to both the detergent SDS, promoted bacterial autoaggregation, increased surface hydrophobicity and affected bacterial virulence and OMV protein sorting (126). Notably, phase variation of H. pylori fucosyltransferases, and consequently the glycosylation pattern of the LPS has previously been identified to occur in high frequencies, with in-vitro studies demonstrating the expression of Le x can vary at a frequency of 0.2-0.5% resulting in differing LPS variants in the same population.…”
Section: H Pylori Lps Structural Diversity In Infection and Immune Ev...mentioning
confidence: 99%